Nondestructive evaluation of heat trap mechanism in coconut oil—a thermal lens study. (7th September 2018) - Raj, Vimal; Soumya, S; Swapna, M S; Sankararaman, S
Abstract: Search for low-cost thermal energy storage (TES) materials has emerged as the recent focus of research. The present work brings out the possible use of the futile repeatedly heated coconut oil for heat trap applications through the sensitive and nondestructive thermal lens technique. Coconut oil repeatedly heated to its smoke point using a temperature controlled heating mantle are subjected to laser-induced thermal lens study to understand the variations in its thermal inertia. The thermal diffusivity of the oil is found to fall by 73.5% of its initial value on repeated heating. The spectroscopic analysis with UV Visible near infrared technique indicates the enhanced optical energy absorption with a bathochromic shift and the Fourier Transform Infrared study points to the structural stability.